Environmental impact and phenotypic stability in potato clones resistant to late blight Phytophthora infestans (Mont) de Bary, resilient to climate change in Peru - Gastelo, M.; Bastos, C.; Ortiz, R.; Blas, R. (2025)
Potato is one of the three most important foods in the world’s diet and is staple in the Peruvian highlands. This crop is affected by late blight, a disease that if not controlled in time can decimate production. The oomycete (Phytophthora infestans) causing this disease is controlled using fungicides, which affect the environment and human health, another form of control is the use of resistant cultivars. 30 potato clones from the LBHTC2 population were evaluated, with the objective of selecting clones with high levels of resistance to this disease, stable for tuber yield, low environmental impact and high economic profitability. The clones were planted in three field experiments in the 2021–2022 growing season. Two experiments with and without late blight chemical control in Oxapampa and Huánuco and one experiment under normal conditions of a potato crop in El Mantaro, Junin, using randomized complete blocks with three replications. The cultivars Yungay, Amarilis and Kory were used as controls for late blight resistance and tuber yield. Late blight resistance and environmental impact were determined based on experiments with and without control in Huánuco and Oxapampa. Yield stability and economic profitability were evaluated based on information from the three experiments. Clones CIP316375.102, CIP316361.187, CIP316367.117, CIP316356.149, CIP316367.147 were the ones that presented the highest yields, high Late blight resistance, phenotypically stable for tuber yield, with low environmental impact and high economic profitability, superior to control cultivars. These clones have high potential for sustainable production systems that allow reducing environmental impact, increasing economic profitability and improving producers’ living standards.